\[ \begin{array}{l}\text { Solve the equation for } y \text {. Write the answer in } y=m x+b \text { form. } \\ y+3=-\frac{1}{3}(x-4)\end{array} \] \( y=\square \) (Use integers or fractions for any numbers in the expression.)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To solve the equation for \( y \), start with the original equation: \[ y + 3 = -\frac{1}{3}(x - 4) \] First, distribute the \(-\frac{1}{3}\): \[ y + 3 = -\frac{1}{3}x + \frac{4}{3} \] Next, isolate \( y \) by subtracting 3 from both sides: \[ y = -\frac{1}{3}x + \frac{4}{3} - 3 \] Now, convert 3 to a fraction with a denominator of 3: \[ 3 = \frac{9}{3} \] So, we have: \[ y = -\frac{1}{3}x + \frac{4}{3} - \frac{9}{3} \] Combining the constants gives: \[ y = -\frac{1}{3}x - \frac{5}{3} \] Thus, in slope-intercept form \( y = mx + b \), the solution is: \[ y = -\frac{1}{3}x - \frac{5}{3} \]